Dynamics of optical solitons in dual-core fibers via two integration schemes. (June 2017) - Arnous, A.H.; Mahmood, S.A.; Younis, M.
Abstract: This article studies the dynamics of optical solitons in dual-core fibers with group velocity mismatch, group velocity dispersion and linear coupling coefficient under Kerr law nonlinearity via two integration schemes, namely, Q -function scheme and trial solution approach. The Q -function scheme extracts dark and singular 1-soliton solutions, along with the corresponding existence restriction. This scheme, however, fails to retrieve bright 1-soliton solution. Moreover, the trial solution approach extracts bright, dark and singular 1-soliton solutions. The constraint conditions, for the existence of the soliton solutions, are also listed. Additionally, a couple of other solutions known as singular periodic solutions, fall out as a by-product of this scheme. The obtained results have potential applications in the study of solitons based optical communication. Highlights: The Schrodinger equations with group velocity mismatch, dispersion and linear coupling coefficient have been considered. Bright, dark soliton solutions are obtained by means of two integration schemes. For the various choices of parameters, different dynamics of solitons are also investigated. The obtained results have potential applications in the study of solitons based in optical communication.